2017
DOI: 10.1056/nejmc1703369
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid in Patients Undergoing Coronary-Artery Surgery

Abstract: 1 found that the risk of death was not significantly higher with tranexamic acid than with placebo among patients undergoing cardiac surgery. This drug has a class IA indication for bleeding prophylaxis, decreasing the use of blood products and the risk of reintervention. Doses that are less than 50 mg per kilogram of body weight are effective in preventing bleeding as well as in decreasing the inflammatory response that is associated with cardiopulmonary bypass. 2Patients with the 5G/G genotype had a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Cardiopulmonary bypass (CPB) initiated during cardiac surgery was demonstrated to activate clotting, exhaust coagulation factors, and cause platelet dysfunction and excessive fibrinolysis (3). Many clinical trials have demonstrated the effectiveness of TXA to maintain hemostasis in on-pump CABG (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiopulmonary bypass (CPB) initiated during cardiac surgery was demonstrated to activate clotting, exhaust coagulation factors, and cause platelet dysfunction and excessive fibrinolysis (3). Many clinical trials have demonstrated the effectiveness of TXA to maintain hemostasis in on-pump CABG (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that TXA does not increase the risk of thromboembolic events. The following are a few examples: a study of orthopedic lower limb procedures, 17 the Aspirin and Tranexamic Acid for Coronary Artery Surgery trial, 18 and an excellent systematic review, meta-analysis, and meta-regression published by Taeuber et al 19 that included 216 trials investigating thromboembolic complications in intravenous (IV) TXA cohorts. Mild side effects of TXA include nausea and diarrhea; however, these effects were observed in 12% of patients in a trial on heavy menstrual bleeding with a dosage of 1 g 4 times daily for 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies [ 81 , 82 , 83 , 84 , 85 ], individual heparin and protamine titration using an automated heparin titration device (Hepcon ® Hemostasis Management System, Medtronic, Minneapolis, MN, USA) was associated with decreased blood loss and transfusion requirements compared to a standard ACT management. However, bleeding and transfusion were secondary end points in these studies and larger multicenter studies are required [ 77 ].…”
Section: Challenges In the Intra-operative Phasementioning
confidence: 99%